Clustering of Rainfall Stations in RH-24 Mexico Region Using the Hurst Exponent in Semivariograms - Benavides Bravo, Francisco Gerardo; Almaguer Martínez, Francisco Javier; Soto Villalobos, Roberto; Tercero Gómez, Víctor; Morales Castillo, Javier (2015)
An important topic in the study of the time series behavior and, in particular, meteorological time series is the long-range dependence. This paper explores the behavior of rainfall variations in different periods, using long-range correlations analysis. Semivariograms and Hurst exponent were applied to historical data in different pluviometric stations of the R´ıo Bravo-San Juan watershed, at the hydrographic RH-24 Mexico region.The database was provided by theWater National Commission (CONAGUA). Using the semivariograms, the Hurst exponent was obtained and used as an input to perform a cluster analysis of rainfall stations. Groups of homogeneous samples that might be useful in a regional frequency analysis were obtained through the process.